A delimitação do estado puerperal para caracterização do infanticídio: leituras médica, psicológica e jurídica - Boskovitz, Luca Zuccari (2023)
Introduction: the puerperal state is a clinical case derivative from puerperium of a sub-jective and singular character that, when severe, affects the postpartum woman in a way which obnubilates her consciousness and annuls her volition, leaving her vulnerable to have thoughts and/or commits extreme atitudes, as like killing her own child, in order to externalize her feeling of refusal/repulse/hesitation by the infant. The duration of this state, however, is uncertain, since it’s directly harnessed to such mom’s internal factors (selflessness of motherhood) as well as external ones (family, social and economic envi-ronment). Objectives: the study of the puerperal state to estimate its duration and, the-refore, estipulate the majors and minors deegrees of influence capable of causing related psychological disorders, in addition to understanding the externalities that subjects wo-men to the noted condition of social and moral vulnerability. Method: documental, bi-bliographical and applied research, of a descriptive and qualitative nature and of a non-experimental cross-sectional study with a retrospective observational character. The research has contented in extracting five lawsuits involving the death of the infant by his mother and, compulsing the material collected from the cases files, proceeded to the analysis of the factual situation portrayed through the mother’s, officer’s involved in the situation and closest friends and family members’ testimonies, besides available medial reports and mother’s historical life data. With the informations in hand, the cases were submitted to the Infanticide’s Mental Status Questionnaire to verify their clinical condi-tions. Finally, the answers were crossed with the researched bibliographical content. Results: the studies pointed to a uncertainty in the exact delimitation of the puerperal state in terms of its duration, as it is strongly linked to the subjectivity of each woman. However, there was a greater influence of this state in periods immediately after child-birth, mainly because the presence of the hormonal peak and moment of greater tension. In at least four of the five cases studied, certain similarities were observed in the contex-to in which the mother is inserted, which are: 1. lower social class, 2. disrupted family, 3. fear of low or none family’s support for her pregnancy, 4. absent baby’s father figure, 5. unwanted pregnancy and 6. mother’s age normally between 18 and 25 years. Conclu-sion: The lack of social and family support generates a self-confidence debilitation in the pregnant woman and, allied to the absence of the infant’s father figure, lets her vul-nerable to the psychic alterations caused by the puerperal state and, therefore, have your rational volition inhibited in favor of extreme thoughts that, if not treated preventively, could lead to the baby’s assassination. The puerperal state, as it is directly connected to the woman’s essence, cannot have its duration precisely defined, once it is subject to its most variable singularities. However, for purposes of punishment in the legal environ-ment, must be given na expansive interpretation to the article 123 of the Penal Code in order to also encompass women who commit infanticide days, or even weeks, after childbirth — since they are influenced by the puerperal state